Co-delivery of isotretinoin and clindamycin by phospholipid-based mixed micellar system confers synergistic effect for treatment of acne vulgaris. (2nd September 2021) - Sharma, Gajanand; Yachha, Yukhti; Thakur, Kanika; Mahajan, Akanksha; Kaur, Gurjeet; Singh, Bhupinder; Raza, Kaisar; Katare, OP
Abstract: Background: The combination therapy of Isotretinoin (ITR) and antibacterial formulations administered through topical route suffer from several limitations including reduced therapeutic efficacy and low patient-compliance. Experiment: The present study aimed to develop biocompatible lipid-based mixed micelles of ITR in combination with Clindamycin phosphate (CLIN) employing self-assembly method to improve its skin delivery, photostability, biocompatibility and pharmacodynamic efficacy. Results: The MTT assay and cellular uptake studies showed non-cytotoxic effect to HaCat cell lines. The zone of inhibition studies conducted in Propionibacterium acnes provides the first literature evidence to support the antimicrobial property of Isotretinoin and Tretinioin. The nano-sized carriers offered (19.3 ± 1.03 nm particle size with −3.12 mV zeta potential) enhanced permeation, skin retention, pre-clinical efficacy and significant skin biocompatibility. The testosterone-induced acne model proved superior pharmacodynamic efficacy of lab developed formulation vis-à-vis marketed products of both the drugs. The results were further confirmed by the histopathological studies of respective skin samples treated with different formulations. Conclusion: The lab developed lipid-based micellar formulation of ITR and CLIN offers a better strategy for the combined delivery of unstable molecules like ITR and CLIN in acne management. ABSTRACT: uf0001